The Effect of Work Experience, Work Environment, and Workload on Employee Productivity Through Work Discipline at The BMCKTR (Bina Marga, Cipta Karya and Tata Ruang) Office of West Sumatera Barat - Anggela Chandini; Zefriyenni; Lusiana (Riset Sinergi Indonesia, 2025)
The purpose of this study is to determine the extent to which work experience, work environment, and workload affect employee productivity through work discipline at the BMCKTR (Bina Marga, Cipta Karya, and Tata Ruang) Office of West Sumatera Province. The research method used is a quantitative approach with an associative design. Data collection techniques included observation, interviews, and questionnaires. The research sample consisted of 76 employees selected using non-probability sampling with random sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Square (PLS). The research results indicate that: Work Experience has a positive and significant effect on Work Discipline, Work Environment has a positive and significant effect on Work Discipline, Workload has a positive but insignificant effect on Work Discipline, Work Experience has a positive but insignificant effect on Productivity, and Work Environment has a positive and significant effect on Productivity. Workload has a positive but insignificant effect on Productivity, while Work Discipline has a positive and significant effect on Productivity. On the other hand, Work Discipline can mediate the relationship between Work Experience and Work Environment on Productivity, but Work Discipline cannot mediate the relationship between Workload and Productivity.